2023
DOI: 10.1097/hs9.0000000000000957
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications and Dynamics of Clonal Hematopoiesis in Anti-CD19 CAR T-cell Treated Patients

Victoria Panagiota,
Johanna Franziska Kerschbaum,
Olaf Penack
et al.

Abstract: Recent evidence revealed important interactions between clonal hematopoiesis (CH) and cellular therapies established for the treatment of hematologic malignancies. The impact of CH on safety, efficacy, and outcome of chimeric antigen receptor (CAR) T-cell therapy is currently under investigation. We analyzed 110 patients with relapsed/refractory B-cell non-Hodgkin lymphoma (n = 105) or acute lymphoblastic leukemia (ALL) (n = 5), treated with Axicabtagene-Ciloleucel (39%), Tisagenlecleucel (51%), or Brexucabtag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 35 publications
(101 reference statements)
0
3
0
Order By: Relevance
“…The high frequency of myeloid neoplasms should be interpreted in the context of the substantial treatment burden in patients receiving CAR-T therapy, including exposure to prior tumorigenic therapies. Additionally, CAR-T therapy might facilitate progression of preexisting clonal hematopoiesis to overt myeloid neoplasia . Extended survival also allows more time for SPMN development.…”
Section: Discussionmentioning
confidence: 99%
“…The high frequency of myeloid neoplasms should be interpreted in the context of the substantial treatment burden in patients receiving CAR-T therapy, including exposure to prior tumorigenic therapies. Additionally, CAR-T therapy might facilitate progression of preexisting clonal hematopoiesis to overt myeloid neoplasia . Extended survival also allows more time for SPMN development.…”
Section: Discussionmentioning
confidence: 99%
“…94 Supporting this hypothesis, a recent study found a high prevalence of clonal hematopoiesis of 50-60% at time of CAR-T infusion. 95,96 Nonetheless, considering the growing body of evidence elucidating the role of in ammatory stressors for clonal expansion, 97,98 the impact of CAR-T induced in ammatory stress on the development of secondary myeloid malignancies warrants future systematic study.…”
Section: Discussionmentioning
confidence: 99%
“…16 However, >95% of CARTITUDE-1 participants had received prior lenalidomide, a drug known to predispose patients to myeloid malignancies through its effects on hematopoietic progenitor cells. 17 , 18 In general, clonal hematopoiesis of indeterminate potential is present in 20% to 60% of patients at baseline before receiving CAR T. 19 , 20 , 21 …”
mentioning
confidence: 99%